Effects of a polyherbal formulation on inflammation and histopathological alterations in mice with ovalbumin-induced allergic asthma - Maryam Hamzeloo-Moghadam; Sayyed Shamsadin Athari; Hanieh Kashafroodi; Tahereh Dargahi; Leila Ara; Rasool Choopani (Mashhad University of Medical Sciences, 2022)
Objective: Allergic asthma is a complex inflammatory disorder that affects the airways. As an ancient medical system, Iranian Traditional Medicine (ITM) recommends a polyherbal formula called "Monzej-e-balgham" for the treatment of asthma. In the present investigation, the antiasthmatic effects of "Monzej-e-balgham" were examined in a murine model of allergic asthma.Materials and Methods: Twenty-eight Balb/c mice weighing 15-20 g were allocated into 4 groups. As negative and positive controls, groups I and II received phosphate-buffered saline (PBS) and ovalbumin (OVA) solutions, respectively. Groups III and IV were first sensitized with OVA and then respectively treated with "Monzej-e-balgham" (63 mg/kg) and budesonide. Finally, bronchoalveolar lavage fluid (BALF) and lung tissues of the animals were collected and used for eosinophil counting, Th2 type interleukins (IL-5, IL-13, and IL-33) measurement, and histological examinations.Results: "Monzej-e-balgham" significantly reduced the number of eosinophils and the levels of IL-5, IL-13, and IL-33 in BALF specimens compared to OVA-sensitized group (p<0.05). It also ameliorated histopathological changes of the lung tissues such as goblet cells hyperplasia and mucus overproduction in comparison to group II. Interestingly, the results of the "Monzej-e-balgham"-treated group were comparable with those obtained for budesonide-inhaled mice.Conclusion: The present data indicated a mechanism that involves Th2 inflammatory responses in allergic asthma and suggested a polyherbal mixture for the treatment of this disease.